2015
DOI: 10.5194/amt-8-4415-2015
|View full text |Cite
|
Sign up to set email alerts
|

On the interpretation of the loading correction of the aethalometer

Abstract: Abstract. Aerosol optical properties were measured with a seven-wavelength aethalometer and a three-wavelength nephelometer at the suburban site SORPES in Nanjing, China, in September 2013-January 2015. The aethalometer compensation parameter k, calculated with the Virkkula et al. (2007) method depended on the backscatter fraction, measured with an independent method, the integrating nephelometer. At λ = 660 nm the daily averaged compensation parameter k ≈ 0.0017 ± 0.0002 and 0.0042 ± 0.0013 when backscatter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…Also shown in Fig. 8 are aerosol back-scatter fractions (b) which are related to the size of the aerosol and have been shown to affect Aethalometers (Virkkula et al, 2015). The site that resembles Summit the most, considering α sp , b, and ω 0 is Pallas.…”
Section: Aethalometer Correction Factor For the Arcticmentioning
confidence: 99%
See 3 more Smart Citations
“…Also shown in Fig. 8 are aerosol back-scatter fractions (b) which are related to the size of the aerosol and have been shown to affect Aethalometers (Virkkula et al, 2015). The site that resembles Summit the most, considering α sp , b, and ω 0 is Pallas.…”
Section: Aethalometer Correction Factor For the Arcticmentioning
confidence: 99%
“…As the filter gets loaded with aerosol particles, loading effects come into play. These loading effects change between the filter spots depending on the optical properties of the aerosol that is being deposited on that particular spot (Virkkula et al, 2015) and even during sampling on the same spot (Drinovec et al, 2015).…”
Section: Aethalometer Correction Factor For the Arcticmentioning
confidence: 99%
See 2 more Smart Citations
“…The wavelength of 370 nm was used because studies have found that BrC shows strong light absorption in the near-UV wavelength range (Andreae and Gelencsér, 2006;Hansen and Schnell, 2005). Measurement data at the wavelength of 880 nm were chosen because light absorption at this wavelength normally represents the BC absorption (Virkkula et al, 2015). Regarding the wavelength dependence analysis of BC and BrC, the wavelength near 880 nm is better for the calculation of the AAE of BC because BC is the dominant absorption components in that wavelength range.…”
Section: Introductionmentioning
confidence: 99%